An Exploratory Study of Rater Orientations on Pre-sessional Academic Conference Presentations through Verbal Report Protocols - Braid, Alasdair (2016)
This exploratory study focuses on the Academic Conference Presentation (ACP), a frequent form of speaking assessment in EAP (English for Academic Purposes), but one that is under-researched from a rater’s perspective. This study analyses raters’ perceptions of the ACP performance from four aspects: what type of features are heeded by raters most, i.e. genre, criticality or language features, the construct-relevance of those heeded features (Fulcher, 2003), the clarity and processability of the rating scale, and the types of strategy that raters use to cope with this task. The study uses a retrospective verbal report methodology, as exemplified in the studies of Orr (2002), Brown (2000) and May (2006). It focuses on an ACP summative assessment from an interim pre-sessional course delivered by the EAP Unit of a British university. The verbal reports were carried out with five trained raters who work in the EAP Unit and the data elicited from the verbal reports was triangulated with follow-up interviews with each rater (Dörnyei, 2007). The research found that the raters heeded predominantly construct-relevant features of performance and attended to criticality and genre features more than language features. The rating scale was found to put a processing strain on the raters and used a substantial amount of relativistic (Knoch, 2009) wording. The research also found that several raters made impressionistic judgements of the overall score while the performance was in progress, but then checked this against the criteria, or against the details of the unfolding performance. There were differences in terms of the philosophies of two raters, with one rater rewarding positive features of performance to counterbalance negative features while another rater adhered more strictly to the rating scale. However, the rating approaches exhibited by the raters were complex and did not fit neatly into the synthetic and analytic types outlined by Pollitt and Murray (1996).